Effect of Vanadium Compounds on the Lipid Organization of Liposomes and Cell Membranes - Bakás, Laura Susana (2001)
The influence of vanadate on the adsorption properties of Merocyanine 540 (MC540) to UMR cells was studied by means of specrofluorometry. An increment in the fluorescence was observed in the osteoblasts incubated with 0.1 mM vanadate. This effect could be interpreted in terms of vanadate inhibitory effects on aminotraslocase activity. However, vanadate promotes a similar behavior to that found in UMR 106 cells when it was added to lipid vesicles composed of phosphatidylcholine. The effect of vanadium in different oxidation states, such as vanadate(V) and vanadyl(IV) on lipid membrane properties was examined in large unilamellar vesicles by means of spectrofluorometry employing different probes. Merocyanine 540 and 1,6-diphenylhexatriene were used in order to sense the changes at interfacial and hydrophobic core of membranes, respectively. In contrast to vanadate, vanadyl decreased the fluorescence of MC540. Both vanadium compounds slightly perturbed the hydrocarbon core. The results can be interpreted by the specific adsorption of both compounds on the polar head groups of phospholipid and suggest a possible influence of vanadium compounds on the lipid organization of cell membranes.